Making Sense of a Changing Economy : Technology, Markets and Morals. - Nell, Edward (Routledge, 1996)
This text presents an unorthodox view of the current state of economic theory and policies. Deriding the general trend for "econobabble", the author explains the reason why conventional wisdom in economics now seems irrelevant and looks to likely future scenarios.